2018
DOI: 10.1039/c8ra06463f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tetraphenylethylene-based conjugated microporous polymers for detection of nitroaromatic explosive compounds

Abstract: Conjugated microporous polymers (CMPs) containing tetraphenylethylene (TPE) were synthesized via the Suzuki coupling polymerization. The tetrafunctional TPE moiety in the polymer backbone was linked with the difunctional phenylene group to exhibit a porous structure with high fluorescence in the solid state because of aggregation-induced emissive TPE. The porous polymer with a fluorescent TPE group successfully detected nitroaromatic explosive compounds that exhibited fluorescence quenching, in which the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Moreover, those studies indicated the interferences along π-electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45]. The quench of photoluminescence after nitrobenzene (electron acceptor) exposure during the optical sensing applications can be a good experimental proof for this behavior [33,[46][47][48][49].…”
Section: Techniques For Covalent Organic Framework Film Formationmentioning
confidence: 93%
“…Moreover, those studies indicated the interferences along π-electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45]. The quench of photoluminescence after nitrobenzene (electron acceptor) exposure during the optical sensing applications can be a good experimental proof for this behavior [33,[46][47][48][49].…”
Section: Techniques For Covalent Organic Framework Film Formationmentioning
confidence: 93%
“…As an alternative to the direct bonding of TPE units for polymer formation, they can be linked by single conjugated components such as vinylenes, ( 49 ) [ 76 ], acetylenes ( 50 ) [ 76 ], phenylenes ( 51 ) [ 98 ] or phenylenacetylenes ( 52 – 54 ) [ 99 ] These polymers were synthesized by Wittig ( 49 ), Suzuki ( 51 ) or Sonogashira ( 50 , 52 – 54 ) reactions, respectively, and M w and PDI are summarized in Figure 22 . In all cases, except for 51, which, although the authors describe their synthesis, do not report any spectroscopic data, when the joint groups are incorporated, an increase in the conjugation is observed together with the corresponding red shift in the absorption wavelengths.…”
Section: Fully Conjugated Polymersmentioning
confidence: 99%
“…As shown in Tables 1 and 2, the corresponding View Article Online K SV and LOD of PA and Fe is higher than those of some previously reported. [67][68][69][70][71][72][73][74][75][76] Quenching mechanism of metal ions and nitro-aromatic analytes…”
Section: Sensing Of Nitro-aromatic Compoundsmentioning
confidence: 99%